Novel Device for Intraoperative Quantitative Measurements of Extraocular Muscle Tensile Strength - Hyun Jin Shin; Minung Park; Hyunkyoo Kang; Andrew G. Lee (Biosensors)
Understanding the tensile properties of extraocular muscles (EOMs) is crucial for successful strabismus surgery and accurate predictions of surgical outcomes. Assessments of EOM tensile strength are traditionally highly dependent on the expertise of the ophthalmic surgeon, since they involve manually pulling the EOM in opposite directions. This approach only provides subjective measurements that are not quantifiable. Previous quantitative approaches have utilized various devices such as implanted force transducers or dial tension gauges connected to muscle tendons with nylon sutures, but these methods are complex and so are rarely used outside of research settings. Consequently, the goal of this study was to create a quantitative and clinically applicable device for assessing EOM tensile strength. This developed device uses a strabismus hook connected to a strain gauge load cell that measures the tensile force and includes a tilting sensor to ensure that the hook is pulled at a consistent angle when a force is applied. The performance of the device was tested on 22 EOMs in 11 patients with intermittent exotropia during surgery for resecting the medial rectus (MR) and recessing the lateral rectus (LR) under general anesthesia. The measured tensile strengths of the MR and LR were 284.9 ± 58.3 and 278.3 ± 64.6 g (mean ± SD), respectively. In conclusion, the novel device developed in this study for quantitative measurements of EOM tensile strength in clinical settings will facilitate understanding of the pathophysiology of strabismus, as well as of the mechanical properties of the EOMs, and enhance the precision of surgical interventions.